The user concept in the space industry and how this frames satellite missions, with a focus on social development in Africa - Kirkam, Kechil (Department of Electrical Engineering, 2018)
Space-derived data lies untouched in data vaults, while many potential use cases for space applications are not exploited by the space industry. This gap may exist because the conceptualisation of the user in the satellite industry is too narrow, and yet influences the architecture and thence outcomes of a satellite mission. Assumptions about users and markets are not made on the basis of data and market research, in itself typically difficult to obtain, especially in Africa. This results in a lack of understanding of the end user and their social and economic context which feeds back to inadequately scoped requirements in satellite design. The reasons for this are not solely the limited imaginations and culture of practice of satellite engineers, but the structure of the space industry itself and its design frameworks. This limitation has impact especially for developing country applications, where the user and beneficiary concept elide in often unexamined and unchallenged ways. The satellite industry, part of the wider space industry, could borrow usefully from the IT industry in its relationship to the user and methods of deriving user requirements; in fact could consider itself part of the IT/data industry. This study explores the relationship between satellite design and the users of space-derived data, and how this is being affected by new disruptors to the traditional space industry. The implications for potential users in Africa are considered.